Konsep Dasar Algoritma Pemrograman - Riyanti Siregar; Yahfizham Yahfizham (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
In this journal, we analyze the basic concept of programming algorithms, which is the main basis for software development. The algorithm itself is a structured set of steps to solve a problem. Then in this journal the author presents an in-depth explanation of what is meant by algorithm, structure, steps and others. This article uses a descriptive method where the author first analyzes, summarizes and describes different situations, conditions from several different sources which are then collected into an article or writing. Collecting data or information sources is carried out using library research techniques from journals, books or internet media which are used as reference material or references relating to the title discussed, namely the basic concept of programming algorithms with more accurate data and clear sources.